2006
DOI: 10.1097/01.nmd.0000198140.02154.32
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Predictors of Full and Partial Recovery From Generalized Anxiety Disorder in Primary Care Patients

Abstract: The current study examined the naturalistic course of generalized anxiety disorder (GAD) in a sample of 113 primary care patients across a 2-year period. Initial diagnoses were established using structured clinical interviews according to DSM-IV diagnostic criteria. Results indicated that the majority of patients meeting DSM-IV diagnostic criteria for GAD were still symptomatic to some degree after 2 years of follow-up. Rates of full and partial recovery from GAD, however, were found to be higher than those re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 26 publications
(41 reference statements)
5
44
0
5
Order By: Relevance
“…Women with GAD are more likely than men to be unemployed (Angst, Gamma, Baldwin, Ajdacic-Gross, & Rössler, 2009) or to be employed part-time rather than full-time (Steiner et al, 2005). Furthermore, longitudinal studies suggest that females with GAD have worse treatment outcome than do males (Rubio & López-Ibor, 2007), even when controlling for other factors such as depression (Rodriguez, 2006). On the other hand, men are significantly more likely than women to have a comorbid alcohol or substance use disorder and to report that their excessive worry leads to arguments and friction with relatives and friends (Vesga-López et al, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Women with GAD are more likely than men to be unemployed (Angst, Gamma, Baldwin, Ajdacic-Gross, & Rössler, 2009) or to be employed part-time rather than full-time (Steiner et al, 2005). Furthermore, longitudinal studies suggest that females with GAD have worse treatment outcome than do males (Rubio & López-Ibor, 2007), even when controlling for other factors such as depression (Rodriguez, 2006). On the other hand, men are significantly more likely than women to have a comorbid alcohol or substance use disorder and to report that their excessive worry leads to arguments and friction with relatives and friends (Vesga-López et al, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Th is may partly explain the lower remission rate obtained, as older age is associated with poorer treatment outcome (Simon et al 2006). According to some studies, gender also tends to aff ect the course of generalized anxiety in that women are generally associated with lack of recovery (Rodriguez et al 2006). Yet, in the present study, no gender-related diff erences in remission rate were found.…”
Section: Demographic Factorsmentioning
confidence: 97%
“…By contrast, follow-up studies in patient groups demonstrate that anxiety disorders tend to run a chronic course, often over many years, with symptoms fluctuating in severity between periods of remission and relapse, the course of illness varying between disorders [II] (Bruce et al, 2005). Generalised anxiety disorder tends to run a waxing and waning course in non-clinical samples [I] (Angst et al, 2009), and a prolonged course in primary care [I] (Rodriguez et al, 2006): but may also 'switch' to other diagnoses particularly depression and somatoform disorders [II] (Rubio and Lopez-Ibor, 2007a). Social anxiety disorder tends to run a chronic course in primary [I] (Beard et al, 2010) Figure 1.…”
Section: Course Of Anxiety Symptoms and Disordersmentioning
confidence: 99%